Conceptualising demand : a distinctive approach to consumption and practice - Rinkinen, Jenny; Shove, Elizabeth, 1959-; Marsden, Greg (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"This book explores fundamental questions about the very idea of demand: how it is constituted, how it changes and how it might be steered. Conceptualising Demand: A Distinctive Approach to Consumption and Practice explores five core propositions: that demand is derived from social practices, that it is made and not simply met; that it is materially embedded and temporally unfolding; and that it is modulated through many forms of policy and governance. In working through these claims, the book weaves concepts from the sociology of consumption, science and technology studies, policy analyses and social theories of practice together with empirical cases and new research into such topics as the rise of refrigerated foods, the emergence of online shopping, and the transformation of services including those of transport and comfort. In providing an accessible account of the social, material and historical foundations of demand, this book takes a fresh look at a concept that is often taken-for-granted, but that is central to many areas of policy-making and academic research. This innovative volume will be of great interest to students and scholars of consumption, energy and mobility"--
OCLC-licensed vendor bibliographic record.
Keywords: Supply and demand; Consumption (Economics); NATURE / Ecology; SCIENCE / Energy